Martial Arts : 50 movie pack. - Lee, Bruce, 1940-1973.; Van Cleef, Lee, 1925-1989.; Mill Creek Entertainment ([United States] : Mill Creek Entertainment, 2008)
Collection of martial arts films, produced from 1972 to 1989.
Disc 1. Kung Fu-- The invisible fist (1972; 90 min.) -- Kung Fu fever (1979; 80 min.). -- Bloodfight (1989; 100 min.) -- Bruce Lee fights back from the grave (1978; 97 min.) -- Disc 2. Rage of the master (1975; 100 min.) -- The real Bruce Lee (1973; 100 min.) -- The screaming Ninja (1973, 101 min.) -- The master (1984, 80 min.) -- Disc 3. Blood of the dragon (1973; 96 min.) -- The clones of Bruce Lee (1977; 87 min.) -- Deadly kick (1976; 90 min.) -- Fighting ace (1979; 86 min.) -- Disc 4. Dragon Lee vs. The five brothers (1978; 89 min.) -- Fists of Bruce Lee (1978; 90 min.) -- The fighting fists of Shanghai Joe (1972; 94 min.) -- L.A. street fighters (1985; 83 min.). -- Disc 5. Champ against champ (1983; 88 min.) -- y Snake crane secret (1976; 85 min.) -- The Crippled Masters (1979; 90 min.) -- The image of Bruce Lee (1978; 89 min.).
Container: Movie ratings vary. Parental guidance suggested.
DVD.
videodisc.
Keywords: Martial arts -- Drama; Martial arts films; Feature films